The mechanism of decomposition of N-methyl-N-nitrosourea (MNU) in water and a study of its reactions with 2'-deoxyguanosine, 2'-deoxyguanosine 5'-monophosphate and d(GTGCAC) - Golding, B; Bleasdale, C; McGinnis, J; Muller, S; Rees, H; Rees, N; Farmer, P; Watson, W (1997)
The carcinogenicity of N-methyl-N-nitrosourea (MNU) arises, from its ability to methylate DNA, This occurs in an aqueous environment and therefore an appreciation of the mode of decomposition of MNU in water is essential to understanding the mechanism of DNA methylation and its base sequence dependence. The kinetics of MNU hydrolyses are shown to be first order in MNU with a steep rise in rate above pH 8. Using NMR for in situ monitoring of reaction intermediates and products from hydrolyses of [ 13CO]MNU, [ 15NH 2]MNU and [ 13CH 3]MNU, it is proved that base-induced hydrolysis of MNU is initiated by deprotonation at the carbamoyl group. The critical reactive species are shown to be the methyldiazonium ion (Me-N 2 +) and cyanate (NCO -). Investigations of reactions of [ 13CH 3]MNU with 2'-deoxyguanosine (dGuo) and 2-deoxyguanosine 5'-monophosphate (dGuo-5P) showed that: a) the site of methylation of dGuo is highly pH-dependent (relatively more N-1 and O 6-methylation compared to N-7 occurs at higher pH; b) the principal site of methylation of dGuo-5P by MNU is at phosphate; c) incorporation of deuterium into methyl groups occurs in D 2O at higher pH. Methylation of the oligonucleotide d(GT[ 15N]GCAC) by MNU in D 2O showed partial deuteriation of the N 7-methyl groups of the guanines, whilst methylation by MNU in water indicated no significant preference for either guanine with respect to N7-methylation.